ASSESSMENT OF RETURN LOGISTICS AND SERVICE: CASE STUDY (Research Bulletins of the Faculty of Economic Sciences, 2025)
The aim of the article is to evaluate the logistics of returns and service based on the company X, which produces agricultural equipment. The company's problem is the excessive number of returns. The research problem was formulated as to what extent IT systems can reduce the number of returns and improve the service process. The research methods used in the article are literature analysis and the index method of complaints and returns. In 2023, there was a large increase in new orders, which contributed to the increase in returns due to the fault of employees, customers and the manufacturer. In company X, the share of incomplete deliveries increased by 0.24%. Delivery reliability deteriorated minimally - at the level of 96.3%, it offers a high standard of delivery service, ensuring that goods reach the customer and services in the best possible quality while maintaining the principles adopted in the company. Delivery flexibility improved by about 1% compared to 2022. The company took steps to solve the problem related to the excessive number of returns and complaints by implementing Comarch ERP XL software.
Keywords: IT systems, reverse logistics, service, customer service